Leveraging the Situational Analysis, Objectives, Strategy, Tactics, Action, and Control (SOSTAC) Framework to Craft Compelling Digital Marketing Strategies for Boutique X in Bandung, West Java - Marpaung, Aidama Nikku Inamie; Talar, Yulianti (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
The growing interest in online platforms presents a significant opportunity for MSMEs like Boutique X, a clothing store in Bandung, West Java. However, the owners' lack of digital experience limits their ability to effectively manage these platforms. This study aims to enhance consumer purchasing interest using the SOSTAC framework. We conducted an internal analysis of the store's Digital Marketing Capabilities (DMC) and an external analysis using PESTEL and Porter’s Five Forces. A questionnaire was developed to evaluate the significance of each DMC factor in influencing consumer purchasing interest, with 103 respondents providing feedback. This input, along with SMART principles, helped establish five marketing objectives. To meet these objectives, we developed a digital marketing strategy based on the RACE framework, incorporating content marketing, influencer marketing, video marketing, SEO, cross-platform marketing, User-Generated Content (UGC), and paid advertising. Proposed tactics include collaborating with influencers, diversifying content, promoting the Shopee platform, enhancing SEO, and encouraging UGC. These tactics are organized into actionable plans with daily, weekly, monthly, and quarterly schedules, alongside key performance indicators (KPIs) for monitoring progress. The goal is to improve digital marketing effectiveness and boost consumer purchasing interest at Boutique X.